Presenting to Local and Remote Audiences: Design and Use of the TELEP System - Jancke, Gavin; Grudin, Jonathan; Gupta, Anoop (1999)
The current generation of desktop computers and networks are bringing streaming audio and video into widespread use. A small investment allows presentations or lectures to be multicast, enabling passive viewing from offices or rooms. We surveyed experienced viewers of multicast presentations and designed a lightweight system that creates greater awareness in the presentation room of remote viewers and allows remote viewers to interact with the speaker. We report on the design, use, and modification of the system, and discuss design tradeoffs.